Building resilience through improving groundwater management for sustainable agricultural intensification in African Sahel - L. Ciampi; H. J. Plumpton; H. Osbahr; R. J. Cornforth; Celia Petty (CABI Agriculture and Bioscience)
Abstract Background This paper examines the role of improved groundwater access and management in providing opportunities for sustainable agricultural intensification and building the resilience of community farmers in Southern Burkina Faso. The findings contribute to current debates about pathways of commercialisation and adaptation in the African Sahel, especially those seeking to find responses to managing the impacts of climate change and delivering on the Sustainable Development Goals. Methods This paper presents data that has been thematically analysed based on the Framework for Sustainable Intensification developed by Pretty and Bharucha (Ann Bot 114:1571–1596, 2014). The data used includes 144 Vulnerability Baseline Assessments which were conducted at the start of the project with the four target Burkinabe communities (Kado, Poa, Tomo, and Zhilivele), and 33 monitoring interviews and vulnerability assessments from the Burkinabe communities of Poa and Tomo to track progress and behaviour change resulting from the BRAVE project interventions. Results The data analysis showed that Burkinabe communities are already making some use of groundwater to support their agricultural livelihoods; most do this through accessing groundwater from shallow wells. It was also shown that there were improvements in the four main themes Identified by the Sustainable Intensification Framework. These included improved information sharing through increased peer-to-peer learning and improvements in confidence levels; improved social cohesion through reduction in community conflict over water resource management; asset improvements shown by tangible improvement of yields; and increased awareness exemplified by behaviour change. Conclusions Through using the Sustainable Intensification framework, this paper argues that such an approach improves essential aspects of resilience building such as information sharing, improved local governance and increased social capital and income. We argue that such changes provide essential pathways to reducing vulnerability and increasing resilience of at-risk communities in the Sahel, but that national policy alignment and investment is essential for long term change and sustainability.